Effects of Dietary Yeast β-Glucan Supplementation on Meat Quality, Antioxidant Capacity and Gut Microbiota of Finishing Pigs - Linjuan He; Jianxin Guo; Yubo Wang; Lu Wang; Doudou Xu; Enfa Yan; Xin Zhang; Jingdong Yin (MDPI AG, 2022)
Yeast β-glucan is a natural antioxidant and has been reported to improve growth performance of piglets, but its application in improving pork quality is limited. This study investigated the effects of dietary yeast β-glucan supplementation on meat quality, antioxidant capacity and gut microbiota of finishing pigs. In a 40-day experiment, ninety finishing pigs (Duroc × Landrace × Yorkshire, 70.47 ± 0.04 kg) were randomly allocated into five treatments including a basal diet supplemented with 0, 50, 100, 200 and 400 mg/kg yeast β-glucan. Results showed that yeast β-glucan significantly increased pH45 min (linear and quadratic, p < 0.01) and a*45 min (linear, p < 0.05), and reduced cooking loss (linear, p < 0.05) and drip loss (quadratic, p < 0.05) of meat in finishing pigs. Importantly, the 200 mg/kg group exhibited the highest values of pH45 min (p < 0.01) and the lowest values of drip loss (p < 0.05), accompanied by a decreased lactate content (p < 0.05) and glycolytic potential (p < 0.05). Dietary supplementation of 200 mg/kg yeast β-glucan markedly increased catalase (CAT) (p < 0.05), superoxide dismutase (SOD) (p < 0.05) and total antioxidant capacity (T-AOC) (p < 0.01) activities in skeletal muscle. Moreover, WPS-2 abundance was decreased significantly in colonic digesta by 200 mg/kg yeast β-glucan and exhibited a positive association with muscle lactate content and drip loss. Together, dietary 200 mg/kg yeast β-glucan supplementation effectively improved pH value and the water-holding capacity of fresh meat through reducing muscle postmortem glycolysis, increasing antioxidant capacity and altering the gut microbiota composition of finishing pigs.